The role of civil servants in the Danish regions - Rafn, Andreas Holt; Steffensen, Filip Strunge (Politica, 2025)
Over the years, the public has increasingly discussed the role of civil servants in a modern democracy: To what extent can they assist their politicians, and how firmly should they insist on their bureaucratic norms when political demands go against it? A number of studies have looked into this aspect at the state level, but surprisingly few have empirically investigated the Danish regional level. This is puzzling, because there is reason to believe that the low politicization of the Danish regional level influences how civil servants act. Therefore we investigate the role of the civil servant based on 33 interviews with politicians and high ranking civil servants. We find that this role, at the regional level, differs from what former studies have found at the state level. We find that the limited demand for political-tactical advice means that civil servants rarely experience gray zones between bureaucratic norms and responsiveness. Similarly, there are rarely any occasions where political demands challenge their professional competency.